Heart Rate Variability in Patients with Essential Hypertension - Tabassum, Rehnuma; Begum, Noorzahan; Ferdousi, Sultana; Begum, Shelina; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2010)
Background: Essential hypertension may be associated with altered cardiovascular autonomic nerve function. Heart Rate Variability (HRV) analysis is an important tool for quantitative measurement of autonomic nerve activity. Objective: To assess the cardiac autonomic nerve function status in essential hypertension by analyzing time domain measures of heart rate variability. Methods: This cross sectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University from 1st July 2008 to 30th June 2009.For this purpose, 60 hypertensive male patients with age ranged between 40-60 years (group B) were enrolled from the Out Patient Department of Cardiology, BSMMU, Dhaka. Based on treatment received, hypertensive patients were subdivided into group B1 i.e.untreated patients on their 1st day of diagnosis and group B2 i.e.patients with antihypertensive therapy. For comparison, 30 age & sex matched apparently healthy normotensive subjects (group A) were also studied as control group. Time domain measures of Heart Rate Variability (HRV) such as Mean RR intervals, Mean HR, SDNN & RMSSD were assessed by a Polygraph machine to observe both sympathetic and parasympathetic nerve function status. For statistical analysis of data, Independent sample t-test, One-way ANOVA test, were used as applicable. Results: Mean R-R interval SDNN and RMSSD were significantly (P<0.01) lower but mean heart rate was significantly (P<0.01) higher in untreated hypertensive patients than those of normotensive subjects. But differences in all these 4 parameters when compared between control and treated hypertensive patients were found statistically non significant. Conclusion: Impaired cardiac autonomic nerve function characterized by sympathetic overactivity may occur in hypertensive patients. Key words: Mean RR; SDNN; RMSSD; hypertension DOI: 10.3329/jbsp.v5i1.5411 J Bangladesh Soc Physiol. 2010 June; 5(1): 1-7